Comment on "Instabilities of isotropic solutions of active polar filaments" - Ziebert, Falko; Zimmermann, Walter (Physical review letters, 2004)
A Comment on the Letter by Tanniemola B. Liverpool and M. Cristina Marchetti, Phys Rev. Lett. 90, 138102 (2003). The authors of the Letter offer a Reply.